Post-translational modification plays an essential role in the translocation of annexin A1 from the cytoplasm to the cell surface. - Solito, E; Christian, H; Festa, M; Mulla, A; Tierney, T; Flower, R; Buckingham, J (2006)
Annexin A1 (ANXA1) has an important role in cell-cell communication in the host defense and neuroendocrine systems. In both systems, its actions are exerted extracellularly via membrane-bound receptors on adjacent sites after translocation of the protein from the cytoplasm to the cell surface of adjacent cells. This study used molecular, microscopic, and pharmacological approaches to explore the mechanisms underlying the cellular exportation of ANXA1 in TtT/GF (pituitary folliculo-stellate) cells. LPS caused serine-phosphorylation of ANXA1 (ANXA1-S27-PO4) and translocation of the phosphorylated protein to the cell membrane. The fundamental requirement of phosphorylation for membrane translocation was confirmed by immunofluorescence microscopy on cells transfected with wild-type or mutated (S27/A) ANXA1 constructs tagged with enhanced green fluorescence protein. The trafficking of ANXA1-S27-PO4 to the cell surface was dependent on PI3-kinase and MAP-kinase. It also required HMG-coenzyme A and myristoylation. The effects of HMG-coenzyme A blockade were overcome by mevalonic acid (the product of HMG-coenzyme A) and farnesyl-pyrophosphate but not by geranyl-geranylpyrophosphate or cholesterol. Together, these results suggest that serine-27 phosphorylation is essential for the translocation of ANXA1 across the cell membrane and also identify a role for isoprenyl lipids. Such lipids could target consensus sequences in ANXA1. Alternatively, they may target other proteins in the signal transduction cascade (e.g., transporters).